Beyond xMOOCs in healthcare education: study of the feasibility in integrating virtual patient systems and MOOC platforms - Natalia Stathakarou; Nabil Zary; Andrzej A. Kononowicz (PeerJ, 2014)
Background. Massive Open Online Courses (MOOCs) are an emerging trend in online learning. However, their technology is not yet completely adjusted to the needs of healthcare education. Integration of Virtual Patients within MOOCs to increase interactivity and foster clinical reasoning skills training, has been discussed in the past, but not verified by a practical implementation.Objective. To investigate the technical feasibility of integrating MOOCs with Virtual Patients for the purpose of enabling further research into the potential pedagogical benefits of this approach.Methods. We selected OpenEdx and Open Labyrinth as representative constituents of a MOOC platform and Virtual Patient system integration. Based upon our prior experience we selected the most fundamental technical requirement to address. Grounded in the available literature we identified an e-learning standard to guide the integration. We attempted to demonstrate the feasibility of the integration by designing a “proof-of-concept” prototype. The resulting pilot implementation was subject of verification by two test cases.Results. A Single Sign-On mechanism connecting Open Labyrinth with OpenEdx and based on the IMS LTI standard was successfully implemented and verified.Conclusion. We investigated the technical perspective of integrating Virtual Patients with MOOCs. By addressing this crucial technical requirement we set a base for future research on the educational benefits of using virtual patients in MOOCs. This provides new opportunities for integrating specialized software in healthcare education at massive scale.